An agent-based model for seagrass production - Balingit, Ivan Carlo M.
Seagrasses are marine plants that can be found in many parts of the world. Seagrasses have various advantages to the underwater and the environment in general. This includes the ability to absorb carbon from the environment called blue carbon. Certain natural and man-made risks can hinder seagrass growth and consequently, the benefits that they give. An agent-based model is created in order to estimate the dynamics between seagrass and various factors. Such model can help in the development of policies regarding seagrass and marine conservation.